Organising Music Workshops - Stres, Eva (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter explores how music workshops in primary schools can promote the holistic development of pupils. It outlines a ten-step process for planning a music workshop, emphasizes the importance of feedback, and discusses various types of workshops, including those involving music tubes, remote delivery, and examples of best practices from Slovenian primary schools. Organizing a music workshop requires a thoughtful approach, including careful activity planning and tailoring objectives to pupils' abilities. Music workshops serve as a tool to foster creativity and social cohesion among pupils, providing a space for experimentation and the development of new musical ideas. They create an environment where pupils can express themselves freely and take risks without fear of criticism. This chapter offers a comprehensive overview of how music workshops can enrich the school curriculum and contribute to the multidimensional development of pupils.